Analysis of Foreign Exchange GRDP in the Tourism Sector on Income in Batam City - Honey Suvia; Muhammad Azril Akbar; Vina Kristini; Marcelino Marcelino (Eduvest - Journal of Universal Studies, 2021)
Batam City has a strategic location that makes tourists stop by either its business related or travelling. For that reason, Batam City built a lot of beautiful tourism places with affordable price. The tourism sector has an important role in improving the economy of Batam City. However, Covid-19 pandemic impacted negatively towards the sector for almost 2 years. The aim of this research is to see how different the tourism sector in Batam City is before and after the pandemic hits. And own known that research take a result the economic batam has been decrease during several year, and the problem has explain with many indicator hypotasis. This study uses qualitative analysis which will be explained descriptively, the things listed are local income, GRDP, data for foreign tourists in Batam, and graphs as an illustration in the study. From the results of the study, it can be concluded that the development and decline in the GRDP of Batam City through the tourism sector industry which is expected to continue to print foreign exchange for the country continues to experience ups and downs. Conditions can affect the level of income of a region. In terms of tourism in attracting foreign tourists into the country with an increasing number in the previous year, Batam City has a positive GRDP figure so that it continues to experience regional growth.